2016
DOI: 10.1016/j.ajhg.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Amyloidogenic Elements in the 3′ UTRs of Neurofilament Genes Trigger Axonal Neuropathy

Abstract: Abnormal protein aggregation is observed in an expanding number of neurodegenerative diseases. Here, we describe a mechanism for intracellular toxic protein aggregation induced by an unusual mutation event in families affected by axonal neuropathy. These families carry distinct frameshift variants in NEFH (neurofilament heavy), leading to a loss of the terminating codon and translation of the 3' UTR into an extra 40 amino acids. In silico aggregation prediction suggested the terminal 20 residues of the altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 44 publications
7
66
0
1
Order By: Relevance
“…From a pathogenesis perspective, the discovery of frame-shift mutations in the final exon of NEFH in two autosomal dominant CMT2 families, while rare, is of interest as it has identified a novel pathomechanism for CMT2 in which loss of the terminating codon results in the translation of an extra 40 amino acid amyloidogenic motif resulting in protein aggregation [15**]. …”
Section: Introductionmentioning
confidence: 99%
“…From a pathogenesis perspective, the discovery of frame-shift mutations in the final exon of NEFH in two autosomal dominant CMT2 families, while rare, is of interest as it has identified a novel pathomechanism for CMT2 in which loss of the terminating codon results in the translation of an extra 40 amino acid amyloidogenic motif resulting in protein aggregation [15**]. …”
Section: Introductionmentioning
confidence: 99%
“…2). Thus, the expression of mutant NEFH led to aggregation of NEFH protein as in a previous report of mutant NF proteins leading to similar aberrant aggregation [10-12]. …”
Section: Resultsmentioning
confidence: 76%
“…During our preparation of this paper, Rebelo et al [12] reported 2 mutations, a deletion mutation (c.3010–3011delGA; p.Asp1004Glnfs*58) and a duplication mutation (c.3017–3020dup; p.Pro1008Alafs*56) in exon 4 of NEFH , found responsible for CMT disease in 2 families. The authors found a region that can express cryptic amyloidogenic elements (CAEs) in the extended amino acids induced by stop loss variants in NEFH or NEFL and identified that the disordered NF aggregates occurring in Neuro-2a cells had a fibrillary amyloid-like structure.…”
Section: Discussionmentioning
confidence: 99%
“…For the duplication, this is based on the out‐of‐frame nature of the duplicated region, and nonsense‐mediated mRNA decay as the likely consequence (Nagy & Maquat, ). The deletion, which involves the gene's 3’‐end including some coding nucleotides and the stop codon, should entail nonstop‐mediated mRNA decay (Hamby, Thomas, Cooper, & Chuzhanova, ; Rebelo et al., ). By thereby representing bona fide loss‐of‐function alleles, both CNVs thus resemble the majority of already known pathogenic variants in IDUA (Bertola et al., ; Poletto et al., ).…”
Section: Discussionmentioning
confidence: 99%